Biomechanical Comparison of Sacral Fixation Characteristics of Standard S1-Pedicle Screw Fixation versus a Novel Constrained S1-Dual-Screw Anchorage in the S1-Pedicle and S1-Alar Bone. Issue 24 (December 2015) - Mayer, Michael; Stephan, Daniel; Resch, Herbert; Augat, Peter; Auffarth, Alexander; Blocher, Martina; Ernstbrunner, Lukas; Hitzl, Wolfgang; Defossez, Henri; Rouge, Renaud; Koller, Heiko
Abstract : Study Design: Biomechanical Laboratory Study. Objective: Analysis of the biomechanical characteristics of a novel sacral constrained dual-screw fixation device (S1-PALA), combining a S1-pedicle screw and a S1-ala screw, compared to a standard bicortical S1-pedicle screw (S1-PS) fixation. Summary of Background Data: Instrumented fusions to the sacrum are biomechanically challenging and plagued by a high risk of nonunion when S1-PS is used as the sole means of fixation. Thus, lumbopelvic fixation is increasingly selected instead, although associated with a reasonable number of instrumentation-related complications. Methods: Around 30 fresh-frozen human sacral bones were harvested and embedded after CT scans. Instrumentation was conducted in alternating order with bicortical 7.0 mm S1-PS and with the S1-PALA including a S1-PS screw and a S1-ala screw, of 7.0 and 6.0 mm diameter, respectively. Specimens were subjected to cyclic loading with increasing loads (25–250 N) until a maximum of 2000 cycles or displacement >2 mm occurred. All implant sacral units (ISUs) were subject to coaxial pullout tests. Failure load, number of ISUs surpassing 2000 cycles, number of cycles, and loads at failure were recorded and compared. Results: Donors' age averaged 77 ± 14.2 years, and BMD was 115 ± 64.8 mgCA-HA/ml. Total working length of screws implanted was 90 ± 8.6 mm in the S1-PALA group and 46 ± 5 mm in the S1-PS group ( P  = 0.0002). In the S1-PALA group, displacement >2 mm occurred after 845 ± 325 cycles at 149 ± 41 N compared to 512 ± 281 cycles at 106 ± 36 N in the S1-PS group ( P  = 0.004; P  = 0.002). In coaxial pull-out testing, failure load was 2118.1 ± 1166 N at a displacement of 2.5 ± 1 mm in the S1-PALA group compared to 1375.6 ± 750.1 N at a displacement of 1.6 ± 0.5 mm in the S1-PS group ( P  = 0.0007; P  = 0.0003). Conclusion: The novel sacral constrained dual-screw anchorage (S1-PALA) significantly improved holding strength after cyclic loading compared to S1-PS. The S1-PALA demonstrated mechanical potential as a useful adjunct in the armamentarium of lumbosacral fixations indicated in cases that need advanced construct stability, but where instrumentation to the ilium or distal dissection to S2 should be avoided. Level of Evidence: N/A